"Yours in Indian Unity": Moderate National Indigenous Organisations and the U.S.-Canada Border in the Red Power Era. (2nd April 2020) - Humalajoki, Reetta
ABSTRACT: Historiography on the Red Power era has to-date largely focused on the direct action protests of the American Indian Movement, while overlooking the continuing political lobbying and transnational work of more moderate Native rights organisations. This article argues that the National Congress of American Indians in the U.S. and the National Indian Brotherhood in Canada rhetorically challenged the U.S.-Canada border, even establishing a Joint Agreement to foster collaboration across it. However, while their leaders purported to challenge nation-state borders, in practice the collaboration between the two organisations adhered to the settler-colonial structures dominant in North America. Shaped by these federal ties, the exchange was ultimately unable to achieve its aim of working towards self-determination through mutual cooperation. Moderate Indigenous organisations remain dependent on federal structures to operate, thus limiting their ability to effectively organise across settler-state borders.